Anti-Malarial Plants of Jonai, India: an Ethnobotanical Approach - Tonlong WANGPAN; Luk Bahadur CHETRY; Jambey TSERING; Tapi TAKA; Sumpam TANGJANG (Notulae Scientia Biologicae, 2016)
North-East India represents a unique ecosystem with treasured medicinal plant wealth closely related with Folk medicines. A large number of plants having medicinal properties and their folk uses have remained confined to the natives of this region. The tribal community of Jonai, Assam was explored to expose the indigenous herbal remedy for malaria. Sixteen antimalarial plants belonging to 13 families were reported. The analysis revealed highest fidelity level (FL) value for Ajuga integrifolia (100%) followed by Ricinus communis (94%), Alstonia scholaris (88%), Oroxylum indicum (86%) and Achyranthes aspera (82%). The percentage of respondent’s knowledge (PRK) about anti-malarial plants showed Alstonia scholaris as the most commonly known antimalarial species (53%) within this region. Preference ranking (PR) unveiled eight species to be very effective against malarial parasite, which includes Allium sativum, Artemisia indica, Azadirachta indica, Carica papaya, Clerodendrum glandulosum, Ocimum tenuiflorum, Oroxylum indicum, Piper longum and Piper nigrum. All medicine preparations are made using water as the medium and are orally administered in the form of crude extract, powder, juice and decoction. Overall analysis suggested Ajuga integrifolia, Achyranthes aspera, Alstonia scholaris, Artemisia indica, Oroxylum indicum and Ricinus communis to be used for the development of novel, economical, effective and ecofriendly herbal formulations for healthcare management.